Biologic anti-IL17 drugs in erythrodermic psoriasisCapsule Summary - Alessandro Falco, MD; Cristina Mugheddu, MD; Jasmine Anedda, MD; Laura Pizzatti, MD; Alice Tatti, MD; Brunella Conti, MD; Laura Atzori, MD (Elsevier, 2024)
Background: Erythrodermic psoriasis (EP) is a potentially life-threatening disease, and there is currently no consensus regarding its optimal treatment. Biological drugs approved for Psoriasis Vulgaris treatment have been used as alternatives to traditional medications. Objective: To evaluate the clinical response and tolerability of anti- interleukin 17 (IL17) biologic drugs during a 2-year-follow-up. Methods: This was a retrospective prospective study. EP cases, defined as >75% body surface area involvement, in patients ≥18 years old treated with anti-IL17 for at least 6 consecutive months were enrolled and then followed until 104 weeks. Patient characteristics, overall clinical responses, Psoriasis Area Severity Index score changes, and adverse events were analyzed. Results: Sixteen patients met the criteria, of which 50% had achieved the Psoriasis Area Severity Index 100 response at week 12 and in 93.7% at week 24. In the prospective observation of the cohort, 87.5% were still in remission at week 52 and 81.25% at 104 weeks, without adverse events. The 3 patients in whom the treatment was interrupted lost efficacy and were switched to other therapies. Limitations: Only descriptive analysis was conducted due to the limited number of patients. Conclusions: A satisfactory long-term clinical response without adverse effects was observed in this case series, suggesting the interest of anti-IL17 in EP treatment.